Effects of Reading-Writing and Think-Pair-Share Strategies on Secondary School Students’ Performance in Essay Writing in Nigeria - Oguntade, Funmilayo Mabel; Akinwamide, Timothy Kolade (Journal of Education and Training, 2023)
This study investigated the effects of Reading-Writing (RW), Think-Pair-Share (TPS), and combination (RW & TPS) strategies on students’ performance in essay writing in senior secondary schools in Ondo State. The study adopted a quasi-experimental pre-test post-test four-group design as well as a descriptive survey type design. The population for the study comprised all the 25 297 public Senior Secondary School (SSS) II students of the 2019/2020 Session in Ondo State. The sample for this study was 308 SSS II students that were selected from public senior secondary schools, using a multi-stage sampling procedure. The instrument used for this study is the Essay Writing Performance Test (EWPT) which was a standardised WAEC question. The reliability of the instrument was established through the test re-test method and a reliability coefficient of 0.70 was obtained. The data collected were analysed using descriptive and inferential statistics. All hypotheses were tested at a 0.05 level of significance. The performance of students in both experimental and Control Groups in the pre-test was low and did not differ statistically this established the homogeneity of the four groups before the experiment. The result also revealed that it was only in the RW and the combination Groups that there was a significant difference in the pre-test and post-test scores of the test subjects at a 0.05 level of significance. The result also established there was a significant difference in the effects of the strategies of teaching investigated on the performance of the students in essay writing.